Prevalence of Vibrio species on Fish from Pelagic and Demersal Habitats - K., Sudha; Thampuran, Nirmala; P.K., Surendran (Fishery Technology, 2025)
The density and diversity in the vibrio species on the body parts of some commercially important fishes of India were studied with respect to the habitat viz pelagic and demersal. The distribution of vibrios on fish from these habitats showed wide variations both quantitatively and qualitatively. The results indicate that the density of vibrios on the skin and gills may be more in pelagic fish compared to demersal types. However the intestinal count of vibrios is similar in the two categories. The species diversity was more in the demersal fishes particularly in the intestinal samples.The vibrio species were in the order of dominance as V. alginolyticus, V. orientalis, and V. campbelli. Species like V. alginolyticus, V. parahaemolyticus, V. vulnificus and V. mimicus were among the pathogenic species isolated from the fish samples. The study reveals that vibrios constitute a major portion of the total bacterial flora in tropical fish.